EFEKTIVITAS PROGRAM PEMBERDAYAAN MASYARAKAT DI SEKITAR TAMAN NASIONAL GUNUNG MERAPI - , SRI UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gunung Merapi National Park has been implementing community development programs MDK (Model Desa Konservasi) in Turgo Villages. MDK is a village conservation model that implementing in a conservation areas in Indonesia. The purpose of this study was to examine the effectiveness of this community empowerment program. This study is expected to see the results of the performance of community empowerment program that has been done by Gunung Merapi National Park and as a consideration for the next program related to community empowerment. This study uses a quantitative approach to the primary data and secondary data were measured using a measuring instrument which has been prepared in advance of the criteria and indicators of the effectiveness of community empowerment program in conservation areas. Primary data were collected by observation and interviews. Research sample for answered 7 indicators from 18 indicators is determined by 100 % sensus for the members of farmers group and random sampling for non member of farmesr group, secondary data obtained by literature and documents related community empowerment programs in Turgo. Once all the data is obtained , carried the scoring with a Likert scale (gradient from positive to negative) then the results of the total score was divided into 3 classes ineffective, effective and very effective . The results showed that community empowerment programs MDK conducted by Gunung Merapi National Park in Turgo is not effective. Several stages in the implementation of the program is not implemented, the program objectives are not entirely achieved, the target program is not appropriate, the ecological benefits of conservation areas are also not achieved. In addition to the social and economic benefits for local communities Gunung Merapi National Park is also not achieved. Implementation of community empowerment programs should follow all stages of the process has been determined, the appropriate program goals and there are benefits for the areas and the community. This community empowerment program has been doing for 2 years, it can be accepted that this program is not effective.